2017
DOI: 10.1016/j.neurobiolaging.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene-based association study of genes linked to hippocampal sclerosis of aging neuropathology: GRN, TMEM106B, ABCC9, and KCNMB2

Abstract: Hippocampal sclerosis of aging (HS-Aging) is a common neurodegenerative condition associated with dementia. To learn more about genetic risk of HS-Aging pathology, we tested gene-based associations of the GRN, TMEM106B, ABCC9, and KCNMB2 genes, which were reported to be associated with HS-Aging pathology in previous studies. Genetic data were obtained from the Alzheimer’s Disease Genetics Consortium (ADGC), linked to autopsy-derived neuropathological outcomes from the National Alzheimer’s Coordinating Center (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…It is also possible that sex could influence the findings, since men at this age are a minority of the population and power is therefore limited to test for sex differences. Findings by Nelson et al were not adjusted for sex , but given that the analyses by Katsumata et al were adjusted , this explanation is likely to be insufficient. A mechanistic link between LATE‐NC + HS and ABCC9 variation is unclear, and this study did not replicate the previous results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that sex could influence the findings, since men at this age are a minority of the population and power is therefore limited to test for sex differences. Findings by Nelson et al were not adjusted for sex , but given that the analyses by Katsumata et al were adjusted , this explanation is likely to be insufficient. A mechanistic link between LATE‐NC + HS and ABCC9 variation is unclear, and this study did not replicate the previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Progranulin may act as a potential neurotrophic factor whose loss of function may cause neurodegeneration in FTLD‐TDP or other related diseases, and lead to the development of TDP‐43‐positive pathology in LATE‐NC + HS . Progranulin expression may have effects on cleavage and distribution of TDP‐43 . Notably, the polymorphic rs5848 site in the 3'‐untranslated region of GRN , which is associated with variations in progranulin levels and increased risk of LATE‐NC + HS, is also part of a binding site for microRNA miR‐659 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address those SNPs, we used assays for proxy SNPs that are in very close (>.98 r 2 and >.99 D') linkage disequilibrium in human (including European) populations: for rs73069071 (in SLOC1A2/IAPP), rs12301085 was assayed, and for rs9637454 (in KCNMB2), rs12496790 was assayed. For the ABCC9 gene variant, we assessed rs704180, since it has been demonstrated to be associated with HS-Aging pathology (Katsumata et al, 2017;Nelson et al, 2014;Nelson et al, 2015b). Notably, the nearby ABCC9 SNP rs4148651 was found to be an eQTL for SLCO1C1 (Nelson et al, 2016a).…”
Section: Genetic (Snp) Assaysmentioning
confidence: 99%
“…More recent research showed that β2 subunit activity can regulate suprachiasmatic nucleus rhythm and circadian behavior by inactivation of BK currents ( Whitt et al, 2016 ). Also, a SNP (RS9637454) of Kcnmb2 was reported to be strongly associated with hippocampal sclerosis, a comorbid neuropathological feature of AD ( Gibson et al, 2014 ; Katsumata et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%